Compact High Selectivity Patch Antenna Under Triple-Mode Resonance via Loading Symmetrical Slots - Mingli Sun; Qianwen Liu; Lei Zhu (IEEE Open Journal of Antennas and Propagation)
In this article, a compact filtering patch antenna on a single-layer substrate under triplemode resonance is proposed by loading two pairs of stepped slots. Initially, four straight slots are symmetrically etched along the radiation edges of a square patch radiator to reshape the radiation and resonant properties of its two higher-order TM02 and TM12 modes for bandwidth enhancement when maintaining the performances of the fundamental TM10 mode unchanged. Owing to the specific field distributions of the reshaped TM02 and TM12 modes, two radiation nulls can be produced nearby. In order to move the radiation nulls outside the desired passband for highly-sharpened wideband filtering radiation, the straight slots are then properly modified with their stepped ones in configuration. In this context, this proposed single patch antenna not only achieves a wide bandwidth under operation of three reshaped TM02, TM10, and TM12 modes, but also attains good frequency selectivity with the help of two out-of-band radiation nulls. For evident demonstration, the proposed antenna prototype is designed, fabricated and measured. Good agreement between the simulated and measured results, including frequency responses of reflection coefficient and radiation gain, is observed. Compared with other reported patch antennas, the proposed antenna not only holds simple layout and compact size in configuration, but also realizes a wideband filtering radiation performance with high frequency selectivity by virtue of excitation and operation of three resonant modes in a single patch radiator.